(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This article highlights the importance of lease relations in financialstatements prepared on the basis of IFRS in increasing the investment attractiveness of enterprises, the concept of lease based on international standards, as well as the stages of its recognition.